Annexin 1 and neutrophil apoptosis. (1st June 2004) - Perretti, M.; Solito, E.
Abstract : ANXA1 (annexin 1), a member of the 'annexin' family of calcium- and phospholipid-binding proteins, was originally identified as an endogenous mediator of the anti-inflammatory actions of glucocorticoids. However, this protein exerts multiple inhibitory effects on the host inflammatory response, including a preferential regulation of the adhesion step of blood-borne neutrophil within the microenvironment of an inflamed vasculature. It is now emerging that ANXA1 is endowed with other roles, since the protein is abundant in inflammatory exudates as it is produced and released by the extravasated neutrophil. In the present paper, we review the novel proapoptotic effect of ANXA1 and discuss its potential with respect to the pathophysiology of inflammation and leucocyte recruitment.